A Meta-Analysis on the Community of Inquiry Presences and Learning Outcomes in Online and Blended Learning Environments - Martin, Florence; Wu, Tong; Wan, Liyong; Xie, Kui (Online Learning, 2022)
The Community of Inquiry (CoI) framework describes three essential presences (i.e., teaching presence, cognitive presence, and social presence) and how these presences interact in providing an educational experience in online and blended learning environments. This meta-analysis examined 19 empirical studies on the CoI Presences (Teaching Presence, Social Presence, and Cognitive Presence) and their correlations with learning outcomes, including actual learning, perceived learning, and satisfaction. It was found that teaching presence and actual learning were moderately positively correlated, (r = .353). There was a weak correlation between cognitive presence and actual learning, (r = .250) and social presence and actual learning, (r = .199). For the correlation between the presences and perceived learning, cognitive presence and perceived learning was found to be strongly correlated, (r = .663), followed by the moderate correlation between social presence and perceived learning (r = .432), and teaching presence and perceived learning, (r = .392). With respect to satisfaction, the correlation between cognitive presence and satisfaction, (r = .586) and between teaching presence and satisfaction was strong, (r = .510), but the correlation between social presence and satisfaction was moderate, (r = .447). The findings have implications for designers and instructors who design and teach online and blended courses to include these presences.